Uranium(VI) complexation with trans-1, 2-cyclohexanediaminetetraacetic acid in solution: thermodynamic and structural studies. Issue 24 (24th November 2020) - Chen, Wen; Chen, Baihua; Liu, Bijun; Yang, Yuchuan; Tu, Jun; Wei, Hongyuan; Yang, Yanqiu; Li, Xingliang; Luo, Shunzhong
Abstract: Interaction between uranium(VI) and aminopolycarboxylic acids could significantly influence the chemical behavior of uranium(VI) in the processing and disposal of nuclear wastes. Trans -1, 2-cyclohexanediaminetetraacetic acid (CDTA) is a commonly used aminopolycarboxylic acid, but its complexation with uranium(VI) has not been sufficiently studied. In this study, stability constants of CDTA protonation and U(VI)-CDTA complexes at different temperatures were measured by potentiometry. Their enthalpies and entropies were obtained from van't Hoff plots. As a result, four U(VI)-CDTA species, UO2 (H2 CDTA), UO2 (HCDTA) -, UO2 CDTA 2- and UO2 (OH)CDTA 3-, were identified at pH 3-6 and their coordination modes in solution were demonstrated by thermodynamic studies. The proposed coordination modes of UO2 (H2 CDTA) and UO2 (HCDTA) - in solution differ from the reported crystals; the former is bidentate bonding with one carboxylate and the latter is tridentate bonding with iminodicarboxylate. Graphical Abstract: